Periodical Press of Kurgan City, Tobolsk Province of Late XIX — Early XX Centuries - A. A. Mironova (Научный диалог, 2021)
The processes of development of mass media in the county city Kurgan, a large agricultural center of the Tobolsk province, in the late 19th — early 20th centuries are analyzed. The relevance of the study is due to the fact that for the first time in Russian historiography the system of mass media of the Kurgan district, which was known all over the world for its butter-making, is described. A brief description of the life of the city is given, typological and substantive features of periodicals are investigated. The main attention in the article is paid to the broadcast of events taking place in the county and the city by journalists. The novelty ofscientific work lies in identifying the directions of the formation of periodicals in the province. It is argued that in the province, the vector of development of newspapers and magazines is directed from specialized publications to mass ones. The history of interaction between publications created by professionals for professionals and mass-oriented newspapers and leaflets is traced. It is concluded that the materials of the regional periodicals allow expanding the source component on the history of the journalistic style in the Russian literary language and on the history of the economic growth of Russian provinces and counties in the pre-revolutionary period.